Pneumococcal meningitis: epidemiological profile pre- and post-introduction of the pneumococcal 10-valent conjugate vaccine - Tatiane E. Hirose; Eliane M.C.P. Maluf; Cristina O. Rodrigues (Elsevier, 2015)
Objectives: To evaluate the possible effects of the introduction of the pneumococcal conjugate 10-valent vaccine schedule in the state of Parana on pneumococcal meningitis cases and to assess the distribution of serotypes among cases. Method: Cross-sectional study with retrospective data collection of cases of pneumococcal meningitis in the state of Paraná reported to Sistema de Informação de Agravos de Notificação (SINAN), from 1998 to 2011. A total of 1,339 cases of pneumococcal meningitis were analyzed; 1,205 cases from the pre-vaccine period (1998-2009) were compared to 134 cases from the post-vaccine period (2010-2011). Descriptive and comparative statistical analyses (chi-squared test and prevalence ratio) were performed using JMP 5.1.2 statistical software (JMP Statistical Discovery, North Carolina, USA) and EPI INFO 6 (Centers for Disease Control and Prevention, Georgia, EUA). Results: There was a significant reduction in the mean rates of incidence and mortality in the general population. The analysis of cases in the pre- and post-vaccination periods in the age groups covered by vaccination (younger than 2 years) showed significant reductions in incidence rates (6.01 cases/100,000 to 2.49 cases/100,000 individuals) and mortality (1.85 cases/100,000 population to 0.47 cases/100,000 population), while the mean lethality rate did not change significantly. There was a significant reduction in cases whose serotypes are included in the vaccine (80.7% to 53.3%). Conclusion: Even after a short time of use, the 10-valent pneumococcal conjugate vaccine has already had a significant impact in reducing the incidence and mortality of meningitis cases among infants, as well as the reduction of cases whose serotypes are included in the vaccine. Resumo: Objetivos: Avaliar os possíveis efeitos da introdução da vacina pneumocócica conjugada 10 valente no calendário vacinal no Paraná sobre os casos de meningite pneumocócica; avaliar a distribuição dos sorotipos dentre os casos. Método: Estudo observacional, transversal, com coleta de dados retrospectiva dos casos de meningite pneumocócica no Estado do Paraná, notificados ao SINAN, no período de 1998 a 2011. Foram analisados 1339 casos de meningite pneumocócica e comparados os 1205 casos do período pré-vacina (1998 a 2009) com os 134 do período pós-vacina (2010 a 2011). A análise estatística descritiva e comparativa (teste qui-quadrado e razão de prevalência) foi realizada no software de estatística JMP 5.1.2 (JMP Statistical Discovery, Carolina do Norte, EUA) e no Programa EPI INFO 6. Resultados: Observou-se redução significativa das taxas médias de incidência e mortalidade na população geral. A análise dos casos nos períodos pré e pós-vacina nas faixas etárias contempladas pela vacinação (menores de 2 anos) mostrou reduções significativas das taxas de incidência (6,01 casos/100.000 para 2,49 casos/100.000 habitantes), mortalidade (1,85 casos/100.000 habitantes para 0,47 casos/100.000 habitantes), enquanto que a letalidade média não apresentou variação significativa. Houve redução significativa dos casos cujos sorotipos estão incluídos na vacina (80,7% para 53,3%). Conclusão: Mesmo com um tempo reduzido de uso, a vacina pneumocócica conjugada 10 valente já apresentou um impacto relevante na diminuição dos coeficientes de incidência e mortalidade dos casos de meningite entre os lactentes, além de redução de casos cujos sorotipos estão incluídos na vacina. Keywords: Streptococcus pneumoniae, Pneumococcal meningitis, Invasive pneumococcal disease, Vaccines, Palavras-chave: Streptococcus pneumoniae, Meningite pneumocócica, Doença pneumocócica invasiva, Vacinas